Hollow mesoporous carbon@Pt Janus nanomotors with dual response of H2O2 and near-infrared light for active cargo delivery. (December 2019) - Xing, Yi; Zhou, Mengyun; Du, Xin; Li, Xiaoyu; Li, Jianqiang; Xu, Tailin; Zhang, Xueji
Graphical abstract: Janus hollow mesoporous carbon nanomotors with the deposition of Pt nanoparticles onto the half-sphere surface have dual actuated autonomous motion ability of H2 O2 and near-infrared light for active cargo transportation. Highlights: Janus hollow mesoporous carbon nanospheres (HMCNs) based self-propelled system was constructed. Hydrophobic HMCNs achieved a high loading efficiency (1370 mg/g) of doxorubicin drug. Hybrid propulsion of H2 O2 and NIR-light was realized. NIR-light induced motion increased the amount of nanomotors adhering to living cancer cells. Abstract: Mesoporous carbon nanoparticles (NPs) are widely used to construct nano-theranostic systems due to their excellent physicochemical properties. Herein, we introduce these mesoporous NPs as nanocarriers to build self-propelled transport systems. Such nanocarriers are successfully fabricated by depositing Pt NPs onto the half-sphere surface. Compared with conventional silica-based nanomotors, hollow mesoporous carbon nanospheres (HMCNs) based nanomotors can achieve a high loading efficiency (1370 mg/g) of anticancer drug doxorubicin hydrochloride (DOX) due to its hydrophobic nature. The enhanced motion is observed by introducing the NIR-light irradiation due to the local thermophoresis from the upward temperature of HMCNs and also observed by introducing H2 O2 that drives the HMCNs@Pt by the asymmetric decomposition. Interestingly, such enhanced motion also results in the increase of the amount of HMCNs adhering to the surface of living cancer cells, which is beneficial for enhancing the efficiency of drug delivery. This synergetic carbon-based transport system with high cargo loading capacity and dual actuated autonomous motion ability displays immense potential for further functional "smart" devices.